A NARRATIVE INQUIRY OF STUDENTS TEACHERS IDENTITY CONSTRUCTION THROUGH TEACHING PRACTICUM: VOICES FROM SECONDARY SCHOOL CLASSROOM IN INDONESIA - Devi Apriliani (Wiralodra English Journal, 2020)
This study aims to explore the student teachers’ experience while conduct teaching practicum. The study identified how three student teachers construct their teacher identity and explore the proper way that they do to manage the classroom in the placement school. I examined the narratives from three student teachers by sharing stories of their teaching practicum in a secondary school in Indonesia for about a month. This study uses in-depth online interviews, reflective journals, and photovoice to collect the data. The results suggest that teaching practicum can be a way to construct student teachers’ professional identities and lead them to deal with the situation in the classroom during the teaching practicum. Moreover, preceding teaching experience and good relationships with members of the school are essential to carry them out from teaching practicum.